KESANTUNAN BERBAHASA DALAM PERCAKAPAN ANTARMAHASISWA SEMESTER DELAPAN STKIP PGRI PONOROGO - Nugroho, Rahmad; Wardiani, Ririen; Setiawan, Heru (Jurnal Bahasa dan Sastra, 2021)
In communicating, the speaker better uses polite language, because it will maintain speaker’s dignity and respects the hearer. Further, it can create smooth and pleasant communication. The purpose of this study is to find a forms of language politeness and their meaning in conversations among eight semester students of STKIP PGRI Ponorogo in 2019. This research is a descriptive research that uses a qualitative approach. The data collection method used in this study is the observation method. In this study, each speech is analyzed based on the theory of politeness from Leech (in Rahardi, 2005: 59) as follows: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. As a result, the researcher found nine tact maxims, two tact maxim violations, one approbation maxim, two sympathy maxims, one sympathy maxim violation, two generosity maxims, nine consensus maxims, and three modesty maxims.